Legal change in the face of risk averse subjects: A generalization of the theory - Luigi Alberto Franzoni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2019)
This study investigates the optimal nature of law making under uncertainty. I focus on a case in which a harmful activity will be subjected to some regulatory measures (a standard, exposure to liability, or a corrective tax). The benefits and costs of precaution are ex-ante uncertain, and this places a risk burden on both injurers and victims. The optimal policy should, at the same time, strike a balance between benefits and costs of the measures, and attenuate the ex-ante risk. Whether measures should be made stronger or softer depends on the size and the sign of the shocks affecting the parties (positive or negative) and their disposition towards risk. With corrective taxes, it also depends on the elasticity of precautions with respect to the tax rate.
Keywords: K2; 330; egal change; regulation of risk; externalities; cost-benefit analysis; emerging risks